Canning portimão. Proposal of a pedestrian route in Portimão, Portugal - Grade, António (2022)
Being tourism the main driver of the region's economy, the touristic proposal presented here, based on the canning industrial heritage, is original and topical. This proposal includes places, buildings, and neighborhoods of the city linked to the theme of the canning industry, and it was intended to make known this heritage. The suggested pedestrian path aims to provide a visit to the city of Portimão from another point of view and to be a promoter of hiking and, simultaneously, to be another offer of cultural tourism in this city. On the other hand, being an urban route, it can be carried out by several age groups and all year round. It is possible to reach a more in-depth knowledge of the industrial history, as well as the political, social and economic past of Portimão, and simultaneously, of the country itself, through the history of canned fish and of the canning industry, reason why there is a great touristic potential for the proposal. It is intended to sensitize the local community and tourists to the richness of the existing heritage in Portimão, positively influencing their social responsibility, while valuing the city and showing its history. The development of this paper was based on bibliographical research, photographic surveys and visits to the sites related to the subject, to obtain relevant information. However, there were found some contradictions in the consulted bibliographical sources and the disappearance of some records, along with the closure and/or demolition of the existing canneries, made the development of this work difficult